Pengaruh Konversi Minyak Sawit Menjadi Biodiesel dengan Katalis Abu Limbah Boiler - Rahmat, Bayu; Primandari, Sri Rizki Putri (Asian Journal of Science, Technology, Engineering, and Art, 2023)
Biodiesel is one of the various alternative energy options to replace the role of diesel or petroleum. Using the basic ingredient, namely palm oil, which is renewable and more environmentally friendly. The palm oil used is not used cooking oil because the focus of this research is to test the effect of boiler waste ash as a catalyst so that the esterification stage can be skipped and focuses on the transesterification stage. The catalyst commonly used today is a homogeneous catalyst that is produced and has a negative impact if there is too much residual substance. Currently, there is not much use for boiler waste ash so much of it is wasted as waste and it is known that boiler waste ash is alkaline and contains alkaline substances so that it can be used as a heterogeneous catalyst to replace homogeneous catalysts. At this tranesterification stage, two types of treatment are given, namely variations in temperature and catalyst concentration to see the best comparison of the several types of samples. The transesterification stage uses a 1:1 ratio of oil and methanol and the addition of 1% KOH. The results of this stage produce biodiesel with characteristics, namely a density ranging between 854-859 Kg/m3 and a viscosity in the range 3,32-4,47 mm2/s, which meets SNI biodiesel standards. From this research, it can be concluded that boiler waste ash has the potential as a heterogeneous catalyst in making biodiesel, replacing homogeneous catalysts and adding to the processing of palm oil boiler waste.